Kepatuhan Mahasiswa dalam Menjalankan Protokol Kesehatan di Masa Covid-19 - Ilyas Ibrahim (FORIKES, 2022)
Corona virus or severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a virus that attacks the respiratory system. This viral infection is called Covid-19, which causes mild disorders of the respiratory system, severe lung infections and even death. This virus can attack anyone, both children, adults and the elderly. As of July 18, 2021, there were 190,794,652 cases of Covid-19 globally, while in Indonesia there were 2,877,476 positive cases. Various efforts have been made by the government to prevent the transmission of Covid-19, but some people do not comply with health protocols. The purpose of this study was to examine compliance with health protocols for students during the Covid-19 pandemic. This type of research is descriptive quantitative. The sample of this study was 50 semester 5 students of STIKes Maluku Husada. The variable observed was student compliance in carrying out health protocols on campus. Data was collected through filling out questionnaires to reveal health protocol compliance in students. Data were analyzed descriptively in the form of frequency and percentage. The results showed that as many as 42 respondents obeyed in the use of masks, 34 respondents obediently washed their hands, 19 respondents obeyed to keep their distance and 16 respondents obeyed to stay away from the crowd. It was concluded that student compliance in health protocols was not maximized, so socialization was needed about the importance of health protocols to prevent the transmission of Covid-19.Keywords: compliance; health protocols; college student; Covid-19ABSTRAK Virus corona atau severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) merupakan virus yang menyerang sistem pernapasan. Infeksi virus ini disebut Covid-19, yang menyebabkan gangguan ringan pada sistem pernapasan, infeksi paru-paru yang berat hingga kematian. Virus ini bisa menyerang siapa saja, baik anak-anak, orang dewasa dan lansia. Kasus Covid-19 per 18 Juli 2021 secara global sebanyak 190.794.652 kasus, sementara itu di Indonesia tercatat 2.877.476 kasus positif. Berbagai upaya telah dilakukan pemerintah untuk mencegah terjadinya penularan Covid-19, namun sebagian masyarakat tidak patuh terhadap protokol kesehatan. Tujuan penelitian ini adalah untuk mengkaji kepatuhan menjalankan protokol kesehatan pada mahasiswa di masa pandemi Covid-19. Jenis penelitian ini adalah kuantitatif diskriptif. Sampel penelitian ini adalah 50 mahasiswa semester 5 STIKes Maluku Husada. Variabel yang diamati yaitu kepatuhan mahasiswa dalam menjalankan protokol kesehatan di kampus. Data dikumpulkan melalui pengisian kuesioner untuk mengungkap kepatuhan protokol kesehatan pada mahasiswa. Data dianalisis secara deskriptif berupa frekuensi dan persentase. Hasil penelitian menunjukkan bahwa sebanyak 42 responden patuh dalam penggunaan masker, 34 responden patuh mencuci tangan, 19 responden patuh menjaga jarak dan 16 responden patuh menjauhi kerumunan. Disimpulkan bahwa kepatuhan mahasiswa dalam protokol kesehatan belum maksimal, sehingga perlu sosialisasi tentang pentingnya protokol kesehatan untuk mencegah penularan Covid-19.Kata kunci: kepatuhan; protokol kesehatan; mahasiswa; Covid-19